Socioeconomic differences in the cost, availability and quality of healthy food in Sydney - Belinda Crawford; Roy Byun; Emily Mitchell; Susan Thompson; Bin Jalaludin; Siranda Torvaldsen (Elsevier, 2017)
Abstract Objective: To compare the cost of a basket of staple foods, together with the availability and quality of fresh fruit and vegetables, by supermarket store type in high and low socioeconomic suburbs of Sydney. Methods: A food basket survey was undertaken in 100 supermarkets in the 20 highest and 20 lowest socioeconomic suburbs of Sydney. We assessed the cost of 46 foods, the range of 30 fresh fruit and vegetables and the quality of ten fresh fruit and vegetables. Two major supermarket retailers, a discount supermarket chain and independent grocery stores were surveyed. Results: The food basket was significantly cheaper in low compared to high socioeconomic suburbs ($177 vs $189, p<0.01). Discount supermarkets were at least 30% cheaper than other supermarket stores. There were fewer varieties and poorer quality fruit and vegetables in stores in low socioeconomic suburbs. Conclusions: Food basket prices and the availability and quality of fruit and vegetables varied significantly by store type and socioeconomic status of suburb. Implications for public health: A nationwide food and nutrition surveillance system is required to inform public health policy and practice initiatives. In addition to the food retail environment, these initiatives must address the underlying contributors to inequity and food insecurity for disadvantaged groups.